Multi-robot formation control in obstacle environments - Wang, Yuanzhe (2019)
Multi-robot system has wide applications in both civil and military fields, due to its high efficiency for task completion and robustness with respect to robot failures. Formation keeping, which is one of the fundamental tasks for multi-robot control, has been extensively investigated in the past decade, resulting in a large variety of methodologies. However, most of the existing approaches are subject to certain limitations when implemented for addressing real formation control problems, mainly due to practical constraints introduced, such as sensor limitations, obstacle and inter-robot collision avoidance in unknown environments, connectivity maintenance, unavailability of global pose measurements and so forth. This thesis deals with formation control problem for real robot applications by taking practical constraints into account.